1990
DOI: 10.2307/3283015
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence and Intensity of Occurrence of Thelazia skrjabini (Nematoda: Thelazioidea) in Cattle in Central Alberta, Canada

Abstract: The distribution of Thelazia skrjabini in the eyes of cattle was examined from necropsies on 297 animals. Although the overall prevalence in beef cattle (21.5%) was similar to that in dairy cattle (25.7%), in general worms were more abundant in beef than in dairy animals. The worm prevalence was lowest in the months from March to June and highest in September among beef and dairy animals. Thelazia skrjabini was found in 76 (16.8%) eyes from beef, and 23 (16.4%) eyes from dairy cattle. Infections were not rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Therefore, genetic susceptibility or hereditary immune deficiencies cannot be excluded. Similar to this finding, a study from Canada reports younger calves and those over 2 years (the age which cows approach peak production) had highest rate of infestation (Kennedy et al, 1990).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, genetic susceptibility or hereditary immune deficiencies cannot be excluded. Similar to this finding, a study from Canada reports younger calves and those over 2 years (the age which cows approach peak production) had highest rate of infestation (Kennedy et al, 1990).…”
Section: Discussionsupporting
confidence: 78%
“…Reportedly, the prevalence of the infestation in slaughtered animals is 2% (Naem, 2011), however, there are no data on clinical prevalence of the nematodes in the region. In the past, infestation rates of 4.5, 25.7% and 41.9% with different species of Thelazia have been reported for cattle from Australia, Canada and United Kingdom (Arbuckle and Khalil, 1978;Kennedy et al, 1990;Overend, 1983). The differences of the prevalences in different regions may relate to climatic conditions, species of the vector flies (Overend, 1983) and possibly the genetic differences of the parasites themselves.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a low prevalence (3.1%, n=223) in the dry season compared to the rainy season (26.6%, n=248) and they observed that adult cattle were more frequently affected than calves. Similarly, Kennedy et al [9] and Van Aken et al [10] reported high prevalences in adult animals than calves. It is likely that the prevalence in buffaloes could vary with age and season although there has been no study aiming at comparing the prevalence between adult buffaloes and the calves as well as comparing the variation between seasons.…”
mentioning
confidence: 91%